The Effect of Music Therapy on Anxiety in Pre-Anesthesia in the Operation Room of Genteng Hospital Banyuwangi - Katmini; Suryanto (Universitas STRADA Indonesia, 2023)
Background: Pre-anesthesia preparation is very important to minimize risks during surgery. This is because the outcome of surgery depends on the assessment of the patient's condition and the preoperative preparation performed on the pre-anesthetized patient. Music has many benefits for human health and can provide good mental strength for listeners. Purpose: Analyzing anxiety before and after music therapy intervention in pre-anesthesia in the operating room and health education with music therapy for anxiety in pre-anesthesia in the operating room. Methods: The research design was quasi-experimental with a pre and post-approach. The population of all patients who underwent surgery under spinal anesthesia. The samples taken in this study were 15 samples of patients who underwent surgery under spinal anesthesia. The independent variable is music therapy. The independent variable is music therapy. The dependent variable is anxiety. The analysis used is univariate and bivariate. Results: Based on the results of data collection conducted by researchers, there are six subject that represent the results of the study, age, gender , marital status, last education, profession, type of surgery. Conclusion: This study concludes that music therapy can reduce the patient's level of anxiety so that it will divert attention to anxiety (distraction) and provide a sense of relaxation before the patient undergoes spinal anesthesia.